KAJIAN TOKSOPLASMOSIS PADA ITIK : UJI SEROLOGIS DAN GAMBARAN SEL DARAH PUTIH - , PUSPA INTAN PURNAMA SARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Toxoplasmosis is a zoonotic disease caused by parasite Toxoplasma gondii. The ability of T. gondii to infect birds, domestic animals and human through various routes and the wide distribution of the parasite causes a high prevalence of infection in human. This parasite could infect ducks and suggests that comsumption of ducksâ meat may pose a potential threat to human health. The purpose of this research is to determine prevalence of toxoplasmosis in ducks based on serological test and leukocyte profile from seropositive ducks. This research used 30 blood samples from ducks in Bambanglipuro Bantul Yogyakarta. Blood was collected from brachialis vein then split into 2 tube, one effendorf tube with ethylene diamine-tetra acetic acid (EDTA) for leukocyte examination and non-EDTA tube for serological test using Pastorex-ToxoÂ®. Antibodies to T. gondii were found in 16 ducks (53,3%). There is no significant difference for total leukocyte, lymphocytes, heterophils, monocytes and eosinofils between seropositive and seronegative toksoplamosis ducks. Keywords : toxoplasmosis, Toxoplasma gondii, serological test, duck, leukocyte